FRI0616 Cost-effectiveness of swapping strategy for established psoriatic arthritis and immediate versus standard swapping strategy for early psoriatic arthritis. (12th June 2018) - Wu, D.; Xu, T.; Cheng, I. T.; Lam, S.H.M.; Yue, J.; Wong, P.; Li, E. K.; Li, T. K.; Tam, L.-S.
Abstract : Background: For patients with psoriatic arthritis (PsA) failing the first TNF-inhibitor, switching to biologic DMARDs [bDMARDs] with different mechanism of actions (swapping strategy) may be superior than switching to another anti-TNF (cycling strategy) [1, 2] . Objectives: To evaluate the cost-effectiveness of 1) swapping strategy for established PsA and 2) immediate versus standard swapping strategy for early PsA from the Hong Kong (HK) societal perspective Methods: Based on comparative effectiveness from network meta-analysis of randomized controlled trials and treatment-specific withdrawal and serious adverse event rate, a swapping York model with life time horizon was developed to evaluate swapping strategy relative to best supportive care (BSC) for PsA failing the first anti-TNF. Initial response to bDMARDs was determined using the Psoriatic Arthritis Response Criteria. The impact of biologics on the arthritis component of the disease is modelled via a change in the HAQ and the impact of the skin component measured using the Psoriasis Area and Severity Index. The model was specified for two hypothetical subpopulations including patients with 1) established PsA (age=47, HAQ=1.22, figure 1A) received five swapping strategies and 2) early PsA [3] (age=40, HAQ=0.71, figure 1B) received immediate (start bDMARDs after diagnosis) or standard (initially given BSC and then start bDMARDs when HAQ increase to 1.22) use of the most cost-effective swapping strategy. Both subpopulations were further classified according to the level of concomitant psoriasis [mild to moderate psoriasis (MMP, PASI=0.73) or moderate to severe psoriasis (MSP, PASI=12.5)]. All five swapping strategies started with an anti-TNF (infliximab, adalimumab, etanercept, certolizumab or golimumab), followed by secukinuamb 300 mg and then ustekinumab 45 mg. The cost-effectiveness of each strategy was determined using a willingness-to-pay (WTP) threshold of £32, 356/ quality-adjusted life-year (QALY) (HK Gross Domestic Product per capita). Results: For the base-case scenario, all five swapping strategies are cost-effective versus BSC strategy for established PsA, which are associated with greater QALY gain and lower treatment related direct costs, psoriasis cost and productivity loss. In established PsA with MMP and MSP, etanercept swapping strategy is likely to be the most cost-effective strategy with an incremental cost £9, 518.93 and £9, 084.58 per QALY gained over BSC strategy respectively. For early PsA with MMP and MSP, the base-case results indicated that standard etanercept swapping strategy was cost-saving (£-50, 635.74 and £-67, 843.32) and more effective (1.20 and 1.32 QALYs); while immediate etanercept swapping strategy was costlier (£13294.95 and £8986.16), more effective (3.82 and 3.27 QALY), and had relative low ICER (£3482.36 and £2745.35 per QALY gained) relative to BSC strategy. Conclusions: Swapping strategy showed favorable cost-effectiveness for established PsA as well as early PsA. The increased costs of biologic agents are offset by the gain in benefits from long-term HAQ reduction. References: [1] Merola JF, et al. Semin Arthritis Rheum2017;47:29–37. [2] Cantini F, et al. Semin Arthritis Rheum2017;47:183–192. [3] Kane D, et al. Rheumatology (Oxford)2003;42:1460–8. Disclosure of Interest: None declared